ٍEvaluating Baremoom Mouthwash Efficacy in Treatment of Chemotherapy-Induced Mucositis - MH Akhavan Karbasi; M Forat Yazdi; H Ahadian; M Jalili Sadrabad (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2016)
Introduction: Chemotherapy-induced oral mucositis is regarded as a painful and discomforting chemotherapy complication , affecting patient’s quality of life and endurance to continue the treatment. Hence, treatment of mucositis is of great significance. The present study was conducted to evaluate the effect of Baremoom mouthwash in treatment of chemotherapy-induced mucositis .